Integrated transcriptomic, proteomic and metabolomic analyses revealing the roles of amino acid and sucrose metabolism in augmenting drought tolerance in Agropyron mongolicum - Ma, Xiaoran; Liang, Qingwei; Han, Yusi; Fan, Lu; Yi, Dengxia; Ma, Lin; Tang, Jun; Wang, Xuemin (Frontiers in Plant Science, 2024)
Drought, a major consequence of climate change, initiates molecular interactions among genes, proteins, and metabolites. Agropyron mongolicum a high-quality perennial grass species, exhibits robust drought resistance. However, the molecular mechanism underlying this resistance remaining largely unexplored. In this study, we performed an integrated analysis of the transcriptome, proteome, and metabolome of A. mongolicum under optimal and drought stress conditions. This combined analysis highlighted the pivotal role of transporters in responding to drought stress. Moreover, metabolite profiling indicated that arginine and proline metabolism, as well as the pentose phosphate pathway, are significantly involved in the drought response of A. mongolicum. Additionally, the integrated analysis suggested that proline metabolism and the pentose phosphate pathway are key elements of the drought resistance strategy in A. mongolicum plants. In summary, our research elucidates the drought adaptation mechanisms of A. mongolicum and identifies potential candidate genes for further study.